PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMIK PADA KONSTRUKSI BANGUNAN 1 - neneng rafika ayu; Riyan Arthur; Amos Neolaka (LPPM Universitas Negeri Jakarta, 2019)
The purpose of this research is to develop learning specifically on digital comic media, State University of Jakarta. The rmethod non-test research instruments in the form of student needs analysis questionnaires, feasibility questionnaires to media experts and material experts as well as test questionnaires to lecturers and students or questionnaires. Then at the stage of research and information gathering a needs analysis survey was conducted of students and students about the development of comic learning media to determine the needs and constraints faced by students. The results of the assessment in the form of digital comic product designs amounted to 90% (very good). The number of final average aspects and indicators of the characteristics of learning media amounted to 91.3% (very good / decent). The assessment of the material presented in digital comics media is considered good with results reaching 73%. The results of the product feasibility assessment assessed by 20 students from the Building Engineering Education Study Program were obtained at 91% (very good). Then the material validation and media on digital comic products developed were obtained an average score of 82.33% and included in the excellent category. Therefore the product can be said to be feasible to use. Keywords: Learning Media, Digital Comics, Building Construction.